2004
DOI: 10.1007/s00059-004-2619-8
|View full text |Cite
|
Sign up to set email alerts
|

Natriuretische Peptide?neue diagnostische Marker bei Herzerkrankungen

Abstract: In patients with heart failure, increased wall stretch due to volume and pressure overload leads to an increase in circulating natriuretic peptides (ANP and BNP and their N-terminal fragments NT-proANP and NT-proBNP). Plasma BNP levels commonly considered normal (< 20 pg/ml) are influenced by age, sex, and also by genetic factors. ANP and BNP are synthesized and released by atrial and ventricular myocytes (Figure 1). In subjects with acute dyspnea, a BNP plasma concentration of 100 pg/ml has been established a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
5

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 43 publications
0
11
0
5
Order By: Relevance
“…The right and left ventricles were transected into sections parallel to the atrioventricular sulcus according to the method of heart preparation (16) and placed in 10% buffered formalin for 24 h at room temperature. Further fixation of the tissue and paraffin embedding were carried out according to standard procedures (17). The obtained specimens were stained with hematoxylin-eosin and observed with an optimal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The right and left ventricles were transected into sections parallel to the atrioventricular sulcus according to the method of heart preparation (16) and placed in 10% buffered formalin for 24 h at room temperature. Further fixation of the tissue and paraffin embedding were carried out according to standard procedures (17). The obtained specimens were stained with hematoxylin-eosin and observed with an optimal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…The highly significant relationship to age and gender for both natriuretic peptides found, accords with other studies [13][14][15][16][17][18] . Diuretics, ACE inhibitors, angiotensin receptor antagonists, betablockers and renal impairment have been shown to decrease levels of natriuretic peptides 19 . In the present study, 27 of 82 patients were treated by drugs but only three of these patients showed significantly lower values of NTproBNP and NT-proANP.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies are available which demonstrate possible benefits of repeated determinations of BNP levels to guide further heart failure therapy [1,18]. Only few studies report no changes in BNP levels despite marked clinical improvement [21,25].…”
Section: Discussionmentioning
confidence: 99%